2013
DOI: 10.1614/ipsm-d-12-00063.1
|View full text |Cite
|
Sign up to set email alerts
|

Hand Pulling Following Mowing and Herbicide Treatments Increases Control of Spotted Knapweed (Centaurea stoebe)

Abstract: Extensive areas in the upper Midwest have been invaded by spotted knapweed, and effective management strategies are required to reestablish native plant communities. We examined effects of mowing, mowing plus clopyralid, or mowing plus glyphosate in factorial combination with hand pulling and burning on knapweed abundances on a knapweed-infested site in western Michigan. We applied mowing and herbicide treatments in summer 2008, and seeded all plots with native grasses and forbs in spring 2009. We conducted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 33 publications
3
24
1
Order By: Relevance
“…In addition, based on soil testing performed at the onset of the study (MacDonald et al 2013), we found that while soil properties did not differ significantly among the different treatment combinations, there was a trend toward lower gravel on plots assigned to the pulling treatments (PERMANOVA; F = 3.19, p = 0.09). Since variation in gravel content could affect soil moisture holding capacity and thus plant response, when a significant pulling effect was found, the data were re-analyzed using gravel as a covariate to ensure the apparent treatment effect was not related to underlying variation in soil properties.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…In addition, based on soil testing performed at the onset of the study (MacDonald et al 2013), we found that while soil properties did not differ significantly among the different treatment combinations, there was a trend toward lower gravel on plots assigned to the pulling treatments (PERMANOVA; F = 3.19, p = 0.09). Since variation in gravel content could affect soil moisture holding capacity and thus plant response, when a significant pulling effect was found, the data were re-analyzed using gravel as a covariate to ensure the apparent treatment effect was not related to underlying variation in soil properties.…”
Section: Discussionmentioning
confidence: 85%
“…Knapweed was the dominant invasive plant at our study site prior to the initiation of our study with 60% to 70% cover based upon the total pre-treatment knapweed density (236 ± 16 m-2 SE, , MacDonald et al 2013). Previous studies at this site demonstrated that native grass establishment and fire reintroduction could successfully control knapweed (MacDonald et al 2003(MacDonald et al , 2007, but these approaches resulted in a community with very low native diversity.…”
Section: Study Areamentioning
confidence: 85%
See 3 more Smart Citations